2008
DOI: 10.1097/aog.0b013e31817d53b6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-Isoleucine and L-Valine on Hot Flushes and Serum Homocysteine

Abstract: OBJECTIVE To investigate whether L-isoleucine was effective in the treatment of hot flushes and whether L-isoleucine, L-valine, or the combination of both amino acids reduced fasting serum homocysteine. METHODS After a 1-week baseline period, 100 postmenopausal women experiencing at least five moderate-severe hot flushes per day were randomized with equal probability to one of four groups (phase 1/phase 2): placebo/L-valine, placebo/L-valine and L-isoleucine, L-isoleucine/L-valine, and L-isoleucine/L-valine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Indeed, previous hot flash RCTs of similar power showed no significant baseline hot flash frequency differences among the treatment groups. 10,11,14,16,17 Even if one hypothetically considered baseline hot flash frequency differences between the groups in the Evans et al study, 8 such differences could not explain the variable treatment effects observed over time in this study. In other words, any hypothetical, and historically unlikely, baseline group difference that may have accounted for the observed efficacy at early time points should have also accounted for efficacy at later time points.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, previous hot flash RCTs of similar power showed no significant baseline hot flash frequency differences among the treatment groups. 10,11,14,16,17 Even if one hypothetically considered baseline hot flash frequency differences between the groups in the Evans et al study, 8 such differences could not explain the variable treatment effects observed over time in this study. In other words, any hypothetical, and historically unlikely, baseline group difference that may have accounted for the observed efficacy at early time points should have also accounted for efficacy at later time points.…”
Section: Discussionmentioning
confidence: 59%
“…Of these, 330 were excluded; 59 included fewer than 20 women per study arm and 54 were not an RCT; 126 did not clearly state a sample size calculation; 52 did not measure vasomotor symptoms as the primary outcome; 39 were secondary analysis. Following these exclusions, 214 RCT were included…”
Section: Resultsmentioning
confidence: 99%
“…There were four categories of interventions: soy isoflavones 15-19 , other isoflavones 20-26 , isoflavone combinations 27-29 , and amino acids 30-31 .…”
Section: Resultsmentioning
confidence: 99%